Systém odměňování zaměstnanců a návrhy na jeho zlepšení ve vybrané společnosti - Jurák, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Tato bakalářská práce je zaměřena na systém odměňování zaměstnanců ve vybrané společnosti XY s.r.o. a na návrhy pro jeho zlepšení. Bakalářská práce je rozdělena do tří části. První, teoretická část obsahuje informace z oblasti odměňování zaměstnanců, vycházejících z odborných publikací. Druhá, analytická část zkoumá současný systém odměňování vybrané společnosti, vnitřní a vnější vlivy, které na něj působí. Poslední, návrhová část vychází z analytické části, kde jsou navrženy změny pro zlepšení systému odměňování ve společnosti XY s.r.o.

This Batchelor thesis is in the main focused on a system of remuneration in the chosen company XY s.r.o. and suggestions for system improvement. The Batchelor thesis is divided into three parts. The first one, the theoretical part contains information from the sector of employee remuneration, coming from the professional literature. The second segment, the analytic one research the nowadays system of remuneration in the chosen company and the intern and extern influence, which is affecting it. The last part, the suggest one, comes from the analytic part, where are recomended new changes for inventions system of remuneration in the company XY s.r.o.
Remuneration System for Employees and Suggestions for its Improvement in a Selected Company
Keywords: odměňování; zaměstnanci; zaměstnavatel; mzda; benefity zaměstnanců; the remuneration; employees; the employer; the wage; the benefits for employees